Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae) - Gyulai, Péter; Saldaitis, Aidas (Zootaxa, 2017)
The descriptions of new taxa in Noctuidae are given: a new species of Acronictinae (Subleuconycta sola sp. nov.), and two new subspecies of Noctuinae (Isochlora grumi multirosea ssp. nov.) and Poliinae (Polia atrax vargai ssp. nov.).